Inclusive Islamic Education and the Empowerment of Alpha Women Amidst the Patriarchal Culture of Society in Tuban Regency - Sita Isna Malyuna; Rachmalia Vinda Kusuma; Moh. Saddad Muhibbi (Islamic State University of Madura, 2025)
This study aims to analyze how inclusive Islamic education plays a role in empowering Alpha women amidst the patriarchal culture of Tuban Regency society. This study uses a qualitative approach with data collection techniques through in-depth interviews and documentation with six women active in the education, social, and public sectors, including Tuban Regency Tourism Ambassadors. The results show that Islamic spirituality is the main foundation for women's self-awareness and independence. Inclusive Islamic education serves as a space for identity negotiation, where women learn to interpret Islamic values ​​​​in their social context and negotiate their position in the public sphere. The findings also show that the strategy for empowering women in Tuban is carried out through a socio-spiritual approach that emphasizes the values ​​​​of wisdom and mercy, rather than confrontation. Inclusive Islamic education has proven to be able to foster critical awareness and leadership in women based on faith, knowledge, and morality.